Report of Working Group on Coal and Lignite for the Tenth Five Year Plan (2002-07) - Planning Commission (Planning Commission, 2001)
With deregulation of prices of remaining grades of coal with effect from 1.1.2000, the prices of all grades of coal stand decontrolled. At present private sector participation in coal mining is limited to mines for captive consumption only. A bill to amend the Coal Mines (Nationalisation) Act, 1973 to permit non captive mining has been introduced in Parliament. It is necessary to expedite passage of this legislation to open up the sector for private investment. Private coal mining for commercial supply is essential to supplement the efforts of national coal companies in making available required quantity of coal from domestic sources. There is need to expedite setting up of regulatory authority for resolving any price disputes and allocation of coal blocks both for exploration and exploitation by framing separate rules under Mines and Minerals Development & Regulation (MMDR) Act, 1957 for grant of prospecting license / mining lease etc.
Government of India Ministry of Coal
Government of India Ministry of Coal